The entrepreneurial process along the corporate life cycle - Cassia, Lucio; Meoli, Michele (Piccola Impresa / Small Business, 2009)
In this paper we contribute to the research literature on the entrepreneurial process byinvestigating the relationship between intangible resources, strategic behaviours and corporatelife cycle dynamics. The corporate life cycle model is based on the experience thatfirms evolve in quite a predictable manner facing common problems in the different phasesof their life. A better understanding of how obstacles can be predicted and managed is instrumentalin overcoming difficulties and enhance their development opportunities. Ourfirst aim in this study is to highlight the strategic role of the figures of entrepreneur, managerand capitalist along the life cycle. Second, our research is supportive of the role of entrepreneurshipas an agent of change during advanced phases of the corporate life cycle